Perkiraan Sisa Umur Transformator Distribusi 20 KV di Perusahaan Bumi Waras Group - Wahyu Triatmoko; Trisna Wati (Institut Teknologi Adhi Tama Surabaya, 2023)
Each distribution transformer has a design age determined by the manufacturing company so that the International Electrotechnical Commission (IEC) 354 of 1972 states that if the transformer is loaded stably at its rated power with an ambient temperature of 20 oC, the hot spot temperature of the transformer will reach 98 oC and the life of transformer will reach 20 years or 7300 days with a normal age shrinkage of 0.0137% per day. The cause of the transformer experiencing shrinkage is the loading and ambient temperature. The temperature around the cities of Sidoarjo and Mojokerto has a room temperature of around 30 oC which will cause the transformer to experience a decrease in age. The research method used in this study is a mathematical method. The data used in this research are loading data and cooling oil temperature for 2 PT transformers. Tunas Baru Lampung, Tbk and 3 transformers PT. Alu Script Pratama and the temperature of the environment around the cities of Sidoarjo and Mojokerto. Based on the research results, it was found that the remaining life of the PT. Tunas Baru Lampung, Tbk transformer 1 has a remaining age of 9,921 years and transformer 2 has a remaining age of 9,986 years, for transformer PT. Alu Aksara Pratama transformer 1 has a remaining age of 18,216 years, transformer 2 has a remaining age of 18,266 years and transformer 3 has a remaining age of 9,654 years.